First, remove all the terms from parenthesis being careful to manage the signs of the individual terms correctly:
#-9x^2 - 3x - 8 - 5x^2 - 2x + 5 = 6x^2 - 2x - 7#
Next, subtract #color(red)(6x^2)# and add #color(blue)(2x)# and #color(green)(7)# to each side of the equation to remove all terms from the right side of the equation while keeping the equation balanced:
#-9x^2 - 3x - 8 - 5x^2 - 2x + 5 - color(red)(6x^2) + color(blue)(2x) + color(green)(7) = 6x^2 - 2x - 7 - color(red)(6x^2) + color(blue)(2x) + color(green)(7)#
#-9x^2 - 3x - 8 - 5x^2 - 2x + 5 - color(red)(6x^2) + color(blue)(2x) + color(green)(7) = 6x^2 - color(red)(6x^2) - 2x + color(blue)(2x) - 7 + color(green)(7)#
#-9x^2 - 3x - 8 - 5x^2 - 2x + 5 - color(red)(6x^2) + color(blue)(2x) + color(green)(7) = 0 - 0 - 0#
#-9x^2 - 3x - 8 - 5x^2 - 2x + 5 - 6x^2 + 2x + 7 = 0#
Then, group like terms on the left side of the equation:
#-9x^2 - 5x^2 - 6x^2 - 3x - 2x + 2x - 8 + 5 + 7 = 0#
Now, combine like terms:
#(-9 - 5 - 6)x^2 + (-3 - 2 + 2)x + (-8 + 5 + 7) = 0#
#-20x^2 + (-3)x + 4 = 0#
#-20x^2 - 3x + 4 = 0#